Cinema therapy sebagai intervensi dalam konseling kelompok - Insan Suwanto; Athia Tamyizatun Nisa (Seminar Nasional Bimbingan dan Konseling Jambore Konseling 3)
Group counseling is a helping to individual in a group setting that is both preventive and healing by creating conditions such empathy that enables counselees to reflect itself. Cinematherapy is one form of therapy in addition to medical and mental health problems and life management. Using the film as a catalyst for the psychological process fits in well with the therapeutic effect in group dynamics. Reflection group counseling members about their emotional responses through cinematherapy an additional component that enriches group therapy. By understanding the meaning of a movie scene or a particular character, counselee obtain an effective way to get to know yourself and others. After leaving the group they are able to continue to maintain what they have learned. In this paper using literature study and related research. In addition, part of this paper allows researchers to construct a theoretical framework and methodology